Electric field-biochar integrated anammox system for high-efficiency nitrogen and phosphorus removal under elevated nitrogen concentration shock - Rui Hu; Xue Chen; Wanjiang Li; Yule Han; Shiliang Heng; Jiayi Wang; Yijing Gao; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Chemical Engineering Journal, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

A novel upcycling process of polystyrene wastes into benzaldehyde by catalyst-free laser flash depolymerization and in-line oxidation - Fu-Lu Chang; Lun Chen; Bin Hu; Fu-Rui Chen; Han Yang; Guang-Jian He (Chemical Engineering Journal, 2025)

An overview of extreme weather-epidemic compound disasters - Jianping Huang; Xinbo Lian; Huijun Wang; Tong Zhu; Han Li; Yingjie Zhao; Rui Wang; Danfeng Wang; Wei Yan; Shujuan Hu; Xiaodan Guan; Shanshan Wang (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

An innovative and efficient approach for slope reliability analysis: Machine learning based surrogate modeling with advanced attention mechanisms - Nenghao Huang; Yu Han; Weiwei Xie; Rui Hu; Hao Peng; Guanxian Song; Menglan Wu; Menglong Zhu; Hua Wei; Ming Liang (Engineering Geology, 2025)

Biochar mitigates greenhouse gas emissions from bulk soil in wheat-corn rotation system by inhibiting biochemical decomposition - Debo He; Rui Yang; Yan Fu; Dongni Hu; Han Ma; Xiaoguo Wang; Zhixin Dong; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Trithiocyanuric acid trilithium salt: A low-cost, high-energy, reduction-state organic cathode material based on disulfide bond - Housheng Gong; Han Yan; Rui Wang; Xiaotang Gan; Liang Huang; Zijun Hu; Tingting Yu; Lihan Liu; Zhiping Song (Chemical Engineering Journal, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

TreegrowNet: a completion network for incomplete single tree point cloud from TLS - Tao Zhang; Chunhua Hu; Jiangang Han; Hao Sun; Rui Wang; Zhen Jing (International Journal of Remote Sensing, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Space weathering characteristics of lunar permanently shadowed regions soils: Evidence from experimental simulation - Zixuan Han; Yang Li; Chen Li; Ronghua Pang; Sizhe Zhao; Zhuang Guo; Kairui Tai; Rui Li; Zhenhao Hu; Li Liu (Acta Geochimica, 2025)

Underwater Target Detection with High Accuracy and Speed Based on YOLOv10 - Zhengliang Hu; Le Cheng; Shui Yu; Pan Xu; Peng Zhang; Rui Tian; Jingqi Han (Journal of Marine Science and Engineering, 2025)
Underwater target detection exhibits extensive applications in marine target exploration and marine environmental monitoring. However, conventional images of underwater targets present challenges including blurred contour information, complex environmental conditions, and pronounced scattering effects. In this work, an underwater target detection method based on YOLOv10 is designed, and the detection performance is compared with the YOLOv5 model. Experimental results demonstrate that the YOLOv10 model has a mAP50 of 85.6% on the URPC 2020 dataset, improving the mAP50 by 1.2% than that of YOLOv5. This model exhibits high detection accuracy and high proceeding speed, which provides a promising support for precise and fast underwater target detection.

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)